Targeted Delivery of Chlorin-e6-Loaded Carbon Nanotube-Based Nanobiocomposite to Cancer Stem Cells for Enhanced Photodynamic Therapy - Prabhavathi Sundaram; Sathish Sundar Dhilip Kumar; Heidi Abrahamse (Pharmaceutics)
Background: Globally, colorectal cancer (CRC) is the third-most diagnosed cancer among males and the second-most diagnosed cancer among females. In cancer, stem cells are a subset of neoplastic cells capable of tumorigenesis and exhibit properties like normal stem cells. Moreover, they are resistant to conventional cancer treatments and can repopulate the tumor following treatment. Cancer cells are stimulated to undergo apoptosis by photodynamic therapy (PDT), which involves a light source, a photosensitizer, and reactive oxygen species. Methods: In this study, colon cancer stem cells were isolated from colon cancer cells and characterized using flow cytometry and immunofluorescence techniques. To treat colon cancer stem cells (CCSCs), single-walled carbon nanotubes (SWCNTs) were coupled with hyaluronic acid (HA) and loaded with chlorin-e6 (Ce6). Nanobiocomposite toxicity was assessed using CCSCs with two fluences of 5 J/cm2 and 10 J/cm2. The cellular changes were observed at 24 and 48 h using microscopy, Results: LDH cytotoxicity assay, and cell death induction by annexin propidium iodide assay. An intracellular analysis of reactive oxygen species (ROS) detected oxidative stress within CCSCs. Conclusions: Overall, the results showed that the newly synthesized nanobiocomposite enhanced the ability of PDT to act as a photosensitizer carrier and induced cell death in CCSCs.